Attempt: signs and types - N. Bezugly, Sergej (2021)
The objective of this study was to analyze what was tempted by direct criminal science. A basic investigation is a dialectical approach to the dissemination of legal phenomena and processes, going through gerais scientific methods (systematic and logical methods, analysis and synthesis) and specific scientific methods. The results will show that the attempted crime was part of the objective side of a certain criminal corpus. The beginning of the attempt may coincide as the beginning of the constitutive act of the crime. Furthermore, an attempt is classified by the implementation of the intention as completed and not completed. And, finally, a special kind of attempt is a "futile attempt."An unsuccessful attempt must be subject to responsibility and qualification, bem as a common attempt.